In situ insight into the low-temperature promotion of ZIF-67 in electrocatalytic oxygen evolution reaction - Anna G. Dymerska; Bartosz Środa; Beata Zielińska; Ewa Mijowska (Materials & Design, 2023)
An efficient electrocatalyst is crucial for sustainable hydrogen-fuel production, where cobalt oxyhydroxide is one of the most active catalysts for alkaline water splitting. Here, we designed a series of Co-based catalysts fabricated by direct low-temperature calcination of ZIF-67 for electrocatalytic oxygen evolution reaction (OER). Interestingly, the treatment of the pristine ZIF-67 by the temperature of only 200 °C was found to induce the most electroactive composition with a high electrochemically active surface of 373.5 cm2 and turnover frequency of 129.7 s−1, while a high specific surface area (1745 m2·g−1) is preserved. It resulted in a robust catalyst with a low overpotential of 317.8 mV at 10 mA·cm−2 and accelerated charge transfer, leading to improved performances in electrochemical energy conversion from water. Moreover, using in situ spectroscopy, XRD and microscopic techniques the active intermediates, for example, M-O, M-OH, and M-OOH were revealed and thus the exact mechanism of the reaction was proposed. Due to the formation of active species a lattice oxygen mechanism (LOM) was revealed.